2010
DOI: 10.1136/emj.2009.089961
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression are unrecognised in emergency patients admitted to the observation care unit

Abstract: Although patients presenting to the ED often experience anxiety and depression, these symptoms are poorly detected by ED physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The BDI-II in our study classified 42% of the patients presenting to the UTMC-ED as having mild, moderate or severe depression. This figure is within range of other studies estimating the prevalence of depression using the BDI-II and the Hospital Anxiety and Depression Scales (HADS) questionnaires 4,5…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The BDI-II in our study classified 42% of the patients presenting to the UTMC-ED as having mild, moderate or severe depression. This figure is within range of other studies estimating the prevalence of depression using the BDI-II and the Hospital Anxiety and Depression Scales (HADS) questionnaires 4,5…”
Section: Discussionsupporting
confidence: 83%
“…Studies estimate that 23–30% of ED patients have an underlying factor of depression and greater than 60% of patients with depression are unidentified 4,5,6. In a 2012 report, 79.7% of adults reported visiting the ED due to lack of access to other providers.…”
Section: Discussionmentioning
confidence: 99%
“…Marchesi et al 19 reported that female ED patients had a higher level of general psychological distress than male ED patients. This was also true for specific psychological distress such as depression and anxiety in most studies 12 18 19 23. Higher frequencies in women were also found for symptoms of anxiety 9 23.…”
Section: Resultsmentioning
confidence: 57%
“…This was also true for specific psychological distress such as depression and anxiety in most studies 12 18 19 23. Higher frequencies in women were also found for symptoms of anxiety 9 23. Furthermore, psychologically distressed ED patients were more likely to be separated, divorced or widowed than non-psychologically distressed ED patients 19.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation